Smarter New York City : how city agencies innovate - Almeida, André Corrêa d' (Columbia University Press, 2018)
Innovation is often presented as being in the exclusive domain of the private sector. Yet despite widespread perceptions of public-sector inefficiency, government agencies have much to teach us about how technological and social advances occur. Improving governance at the municipal level is critical to the future of the twenty-first-century city, from environmental sustainability to education, economic development, public health, and beyond. In this age of acceleration and massive migration of people into cities around the world, this book explains how innovation from within city agencies and administrations makes urban systems smarter and shapes life in New York City. Using a series of case studies, Smarter New York City describes the drivers and constraints behind urban innovation, including leadership and organization; networks and interagency collaboration; institutional context; technology and real-time data collection; responsiveness and decision making; and results and impact. Cases include residential organic-waste collection, an NYPD program that identifies the sound of gunshots in real time, and the Vision Zero attempt to end traffic casualties, among others. Challenging the usefulness of a tech-centric view of urban innovation, Smarter New York City brings together a multidisciplinary and integrated perspective to imagine new possibilities from within city agencies, with practical lessons for city officials, urban planners, policy makers, civil society, and potential private-sector partners.